2017
DOI: 10.1002/brb3.629
|View full text |Cite
|
Sign up to set email alerts
|

Internal capsule: The homunculus distribution in the posterior limb

Abstract: IntroductionIn our experience, sometimes, the symptom of patients who suffered from infarction in internal capsule (IC) do not necessarily fit the classical fiber distribution. This study aims to explain this phenomenon.Methods and MaterialsA total of 34 patients with infarction lesions in the IC were included in this study, according to the clinical symptom, divided into three groups, group A (more severe weakness of the foot than the hand), group B (more severe weakness of the hand than the foot) and group C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…It can be noted that even without masking, the pattern of maximum HRF dispersion change occurs over the anatomy of the internal capsule, with a local maximum occurring at the genu, and activation spreading backwards along the posterior limb. Though motor signals from the corticospinal tract are traditionally thought to travel through the posterior limb of the internal capsule, more recent research has debated the exact localization of these representations (Duerden et al, 2011;Qian and Tan, 2017) and the function of the genu (Yim et al, 2013). Evidence from non-human primates using histopathology and retrograde traces from motor areas showed that arm representations are distributed throughout the internal capsule in an overlapping manner, with fibers from the supplementary motor area passing through the genu (Morecraft et al, 2002).…”
Section: Condition Roimentioning
confidence: 99%
“…It can be noted that even without masking, the pattern of maximum HRF dispersion change occurs over the anatomy of the internal capsule, with a local maximum occurring at the genu, and activation spreading backwards along the posterior limb. Though motor signals from the corticospinal tract are traditionally thought to travel through the posterior limb of the internal capsule, more recent research has debated the exact localization of these representations (Duerden et al, 2011;Qian and Tan, 2017) and the function of the genu (Yim et al, 2013). Evidence from non-human primates using histopathology and retrograde traces from motor areas showed that arm representations are distributed throughout the internal capsule in an overlapping manner, with fibers from the supplementary motor area passing through the genu (Morecraft et al, 2002).…”
Section: Condition Roimentioning
confidence: 99%
“…Specifically, the posterior limb of internal capsule hosts sensory fibers of the corticospinal tract leading to motor areas as well as tracts of optic radiation. Additionally, one recent study also demonstrated possible homunculus-like organization of fibers in PIC (Qian and Tan, 2017). Therefore, selective FA increase in hand fibers could be masked by the underlying WM microstructure.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies examining the characteristics of internal capsule relies on findings on cadavers or imaging techniques such as diffusion tensor tractography (DTT) and imaging (DTI), MR and functional MR imaging (fMRI). [4][5][6][7][8][9][10][11][12][13] DTT provides useful data on localization of the parts of the internal capsule as well as the length or vertical angle of fiber tracts composing the internal capsule. DTT can be used to assess white mater tracts both in healthy individuals and in individuals with pathology (stroke, glioblastoma, multiple sclerosis, amyotrophic lateral sclerosis, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7]12,13] MRI and FMRI also provides assessment of detecting pathologies affecting the internal capsule. [9,14] In a recent study by Dos Santos et al [15] brain specimens taken from cadavers stained by a special technique and relationships of the basal nuclei and the internal capsule was described with anatomical coordinates. When all the findings using different imaging techniques compared, it can be seen that the results do not always match.…”
Section: Discussionmentioning
confidence: 99%